2018
DOI: 10.3390/ijerph15030463
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Association of Food Preferences and Self-Reported Psychological Well-Being among Middle-Aged and Older Adults in Contemporary China-Results from the China Health and Nutrition Survey

Abstract: China has undergone rapid social transitions within the last few decades. However, mental health issues, challenges to psychological well-being, and poor dietary choices have gradually surfaced. These health concerns are related to the rapid growth of the aging population and of the fast-paced industrialized society. Nevertheless, there is little knowledge about food preferences and psychological well-being measurements in contemporary China. Applying the 2011 China Health and Nutrition Survey (CHNS) with a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…Self-reported food likes and dislikes appears to capture habitual dietary intake. Food likes connect markers of taste genetics to intake [57,58] or health [30], correlate with self-reported intake [21,[27][28][29][30][31], and associate with biomarkers of consumption [21,32,33] and health outcomes [20][21][22][23][24]32,33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-reported food likes and dislikes appears to capture habitual dietary intake. Food likes connect markers of taste genetics to intake [57,58] or health [30], correlate with self-reported intake [21,[27][28][29][30][31], and associate with biomarkers of consumption [21,32,33] and health outcomes [20][21][22][23][24]32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary histories or FFQ increase the likelihood of capturing usual intake, but may suffer from over/under reporting bias, difficulty of remembering the type and frequency of foods consumed, challenges of converting what is consumed into frequency categories, and participant and researcher cost/time [19]. Liking surveys show promise as a tool to assess dietary intake [20][21][22][23] and for examining related health outcomes [24] based on the assumption that, over time, we tend to eat what we like and avoid what we do not. In some scientific literature, the terms food preference or liking are used interchangeably with food consumption (e.g., [25,26]).…”
Section: Introductionmentioning
confidence: 99%
“…Second, Western-style diets have been widely adopted and accepted as a routine eating pattern in the urban areas, but it is less far-reaching in the rural areas because of lower economic growth and less population density [ 36 ]. Lee and her colleagues reported that Westernized fast food was linked with poorer psychological health status among the Chinese population [ 37 ]. With Western-style diets being more and more integrated into daily lives of urban residents, we are expecting a worrying enlarging gap of mortality between rural and urban patients in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we only used the food preferences data to determine dietary practice. In a way, the food preference can indicate both individuals' food consumption habits and their attitudes for different types of food for long-term than 3-day 24 h dietary recall method (Lee et al, 2018). More various or objective indicators of food consumption should be used in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, research on food preferences should be strengthened with rapid change of dietary. Additionally, only one cross-sectional study examined the relationship between psychological well-being and food preference among adults aged over 45 years (Lee et al, 2018).…”
Section: Introductionmentioning
confidence: 99%